2024
DOI: 10.1002/cphc.202300715
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Naked Metal Clusters for Catalysis

Zhixun Luo,
Aamir Shehzad

Abstract: The properties of sub‐nano metal clusters are governed by quantum confinement and their large surface‐to‐bulk ratios, atomically precise compositions and geometric/electronic structures. Advances in metal clusters lead to new opportunities in diverse aspects of sciences including chemo‐sensing, bio‐imaging, photochemistry and catalysis. Naked metal clusters having synergic multiple active sites and coordinative unsaturation and tunable stability/activity enable researchers to design atomically precise metal ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 350 publications
(169 reference statements)
0
0
0
Order By: Relevance
“…Atomic clusters, as a special phase that appears during the transition of matter from atoms to macroscopic solids, have interesting characteristics such as quantum size effects, unique surface, adjustable composition, and high specific surface area. Thus, clusters are expected to be potential catalysts that combine the advantages of both homogeneous and heterogeneous catalysts . For example, Corma and coworkers reported that small gold clusters (3–10 atoms) formed by conventional gold salts and gold complexes could catalyze various organic reactions at room temperature, which clearly demonstrates the potential of small metal clusters as highly active catalysts for organic synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…Atomic clusters, as a special phase that appears during the transition of matter from atoms to macroscopic solids, have interesting characteristics such as quantum size effects, unique surface, adjustable composition, and high specific surface area. Thus, clusters are expected to be potential catalysts that combine the advantages of both homogeneous and heterogeneous catalysts . For example, Corma and coworkers reported that small gold clusters (3–10 atoms) formed by conventional gold salts and gold complexes could catalyze various organic reactions at room temperature, which clearly demonstrates the potential of small metal clusters as highly active catalysts for organic synthesis.…”
Section: Introductionmentioning
confidence: 99%